MEDIA INFORMATION TECHNOLOGY DALAM PEMBELAJARAN PAI DI SMP NEGERI 1 KARANGKOBAR BANJARNEGARA - Ahmad Pramudianto; Zaenal Sukawi; Ahsin - Wijaya (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2019)
In the digital era like today, information technology is developing very rapidly. In the field of education, information technology can be applied in learning to improve the quality and results of student learning. Therefore, on this occasion the author intends to present a study of the implementation of the Information Technology (IT) media in PAI learning at Karangkobar 1 Public Middle School Banjarnegara. The purpose of this paper is: 1) To describe the planning carried out by the teacher in the implementation of IT media in PAI learning in Karangkobar Banjarnegara 1 Junior High School 2018/2019. 2) To find out the implementation of IT media in PAI learning in Karangkobar Banjarnegara 1 Junior High School 2018/2019. 3) To find out the implications of the implementation of IT media in PAI learning on teachers and students in Karangkobar Banjarnegara 1 Junior High School 2018/2019. This writing uses a qualitative approach with a case study design. Data collection is done by interview, observation and documentation techniques. While data analysis techniques, the author uses data reduction, data presentation and verification. Writing informants are: PAI teachers, ICT teachers, head of the lab. computers, students, head of the sarpras, curriculum curriculum, and principals. The writing results show that: 1) PAI learning planning in Karangkobar Middle School 1 can be mapped into two administrative planning and technical planning. Administrative planning includes planning learning devices such as prota, promissory notes, syllabus and lesson plans. The RPP includes SK, KD, formulation of learning objectives, formulation of indicators of achievement, approaches, methods, strategies, media and evaluation tools. While technical planning means that the teacher prepares technical devices used in supporting the smooth learning such as computers, laptops, LCDs, DVDs and other devices. 2) Implementation of PAI learning using IT media in Karangkobar 1 Public Middle School through: a. Internet. b. Computer program. c. DVDs and the like. 3) Implications of PAI learning using IT media in Karangkobar 1 Public Middle School Banjarnegara including: a. Implications for teachers include; the teacher is better prepared, the teacher easily presents the subject matter, makes the teacher creative and innovative. b. Implications for students include: students learn faster, encourage and motivate, easily understand the subject matter.